Combined administration of microdoses of growth hormone and erythropoietin: Effects on performance and evaluation of GH detection capability using anti‐doping methods. Issue 11 (16th August 2019) - Marchand, Alexandre; Martin, Jean‐Antoine; Collot, David; Hoang, Olivier; Roulland, Ingrid; Semence, Florian; Sottas, Pierre‐Edouard; Audran, Michel; Varlet‐Marie, Emmanuelle
Abstract: The combination of growth hormone (GH) and recombinant erythropoietin (rEPO) is thought to be used particularly in endurance sports. Our objective was to reproduce a 2‐week administration of rEPO microdoses alone or in combination with GH microdoses (three times a week) on healthy and athletic male subjects and to evaluate if GH had any additional effects compared to EPO treatment alone. The effects of the treatments on hematological parameters and VO2max were studied as well as the detection of GH in serum. While the rEPO microdose regimen was associated with a significant increase in reticulocytes, no clear elevation in hemoglobin concentration (HGB) was observed. Using a correction by plasma volume did not reveal more effects of EPO on HGB. Our results did not show any additional effect when the GH microdoses were co‐administered. In addition, no clear increase in VO2max was observed after treatment, with an elevation in only half the subjects in both groups (EPO and EPO+GH). A clear effect of GH on insulin‐like growth factor I (IGF‐I) was seen but it was lower on procollagen III amino‐terminal propeptide (P‐III‐NP). GH detection using the direct isoform test identified only one subject 24 hours after receiving GH. The GH biomarker test combining IGF‐I and P‐III‐NP was not able to detect the GH administration. However, a longitudinal follow‐up of the intraindividual variations showed a significant increase in IGF‐I 24 and 48 hours after GH administration in most subjects, while the effect of GH microdoses on P‐III‐NP was less straightforward. Abstract : Highlights Repeated EPO microdoses increased Ret% but had no clear effect on HGB. GH microdoses did not seem to produce any additional effects to EPO microdoses on erythropoiesis. Microdoses (EPO or EPO and GH) had no clear effect on VO2max. GH could not be detected in serum 24 hours after administration, despite an increase in the GH biomarker IGF‐I, but a longitudinal approach could reveal more easily GH use.